Uso de óleo pós-fritura para produção econômica de bioemulsificante e biotensoativo por mucor hiemalis UCP 0039 isolado de solo da caatinga (PE, Brasil). - Ferreira, Isabela Natalia da Silva (2019)
Surfactants / surfactants are amphiphilic compounds that have as their main feature the ability to reduce surface tension. Emulsifiers do not necessarily reduce surface tension, however they are excellent in their ability to form stable emulsions between immiscible liquids by dispersing the droplets of one liquid into another and preventing them from coalesce. In this context, the present study produced biotensive and bioemulsifier by Mucor hiemalis UCP 0039 in medium containing post-frying soybean oil as a renewable source. To this end, M. hiemalis was grown in medium containing 1% sodium glutamate and 5% post-frying soybean oil under stirring and static conditions. The physical and chemical characteristics of the bioproducts were determined by surface tension, emulsification index, dispersing action and viscosity effect in oils. While the characterization of biotensive and bioemulsifier was performed by ionic charge determination, identification of functional groups and biochemical composition in proteins, carbohydrates and lipids. Modifications of pH, temperature and salinity in metabolic liquids were performed and then the dispersing action and emulsification potential were evaluated to identify their stability. The results show that M. hiemalis biotensive agent was able to reduce the surface tension from 72 mN / m to 32 mN / m, showed 96% emulsification index and 50 cm2 ADO dispersion action, cationic character, and demonstrated ability in reducing the viscosity of hydrophobic compound such as burnt engine oil from 83 cP to 55 cP. On the other hand, the bioemulsifier reduced the surface tension to 40 mN / m, reached an emulsification index of 98%, has an anionic character, provided emulsion stability after temperature change, showed low dispersing action (19 cm2 ADO) and increased viscosity. of the hydrophobic compounds tested. Additionally, the M. hiemalis biotensive agent and bioemulsifier have glycolipid composition. Due to the mentioned potential of the bioemulsifier and biotensive agent produced, it is possible to indicate Mucor hiemalis as an efficient microorganism capable of metabolizing and bioconverting post-frying soybean oil into bioproducts that can be used in the formulation of everyday industrial products. production process that meets the basic requirements of sustainability.